(untitled) (Ta’limning zamonaviy transformatsiyasi, 2024)
From the WHO report for 2020 Until now, the problem of tuberculosis has not been solved in any country in the world and remains a priority public health task. According to WHO data, in 2020, 10.0 million people fell ill in the world , including 5.6 million men, 3.2 million women, 1.2 million children. In 2021 - 9.9 million, including : 5.5 million men, 3.3 million women, 1.1 million children, 1.3 million people with HIV-negative status, died from tuberculosis. 214,000 HIV-positive from tuberculosis. The number of patients with MDR and XDR is growing from year to year. Tuberculosis is still one of the 10 main causes of death from a single pathogen.